Changes in Case-Mix and Health Outcomes of Medicare Fee-for-Service Beneficiaries and Managed Care Enrollees During the Years 1992–2011. Issue 1 (January 2018) - Koroukian, Siran M.; Basu, Jayasree; Schiltz, Nicholas K.; Navale, Suparna; Bakaki, Paul M.; Warner, David F.; Dor, Avi; Given, Charles W.; Stange, Kurt C.
Abstract : Background: Recent studies suggest that managed care enrollees (MCEs) and fee-for-service beneficiaries (FFSBs) have become similar in case-mix over time; but comparisons of health outcomes have yielded mixed results. Objective: To examine changes in differentials between MCEs and FFSBs both in case-mix and health outcomes over time. Design: Temporal study of the linked Health and Retirement Study (HRS) and Medicare data, comparing case-mix and health outcomes between MCEs and FFSBs across 3 time periods: 1992–1998, 1999–2004, and 2005–2011. We used multivariable analysis, stratified by, and pooled across the study periods. The unit of analysis was the person-wave (n=167, 204). Subjects: HRS participants who were also enrolled in Medicare. Measures: Outcome measures included self-reported fair/poor health, 2-year self-rated worse health, and 2-year mortality. Our main covariate was a composite measure of multimorbidity (MM), MM0–MM3, defined as the co-occurrence of chronic conditions, functional limitations, and/or geriatric syndromes. Results: The case-mix differential between MCEs and FFSBs persisted over time. Results from multivariable models on the pooled data and incorporating interaction terms between managed care status and study period indicated that MCEs and FFSBs were as likely to die within 2 years from the HRS interview ( P =0.073). This likelihood remained unchanged across the study periods. However, MCEs were more likely than FFSBs to report fair/poor health in the third study period (change in probability for the interaction term: 0.024, P =0.008), but less likely to rate their health worse in the last 2 years, albeit at borderline significance (change in probability: −0.021, P =0.059). Conclusions: Despite the persistence of selection bias, the differential in self-reported fair/poor status between MCEs and FFSBs seems to be closing over time. Abstract : Supplemental Digital Content is available in the text.